Gendered Food Mapping Data on Matooke generated by NARL & Bioversity in Uganda - Marimo, Pricilla; Akankwasa, Kenneth; Nowakunda, Kephas (2023)
This dataset contains data generated during the Activity 3 or Step 2 - Gendered food mapping performed by the NARL & Bioversity team in Uganda on Matooke, within the RTBfoods project (following the Methodological Guidance).